2020
DOI: 10.1371/journal.pone.0240418
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex biomarker assay improves the diagnostic performance of HE4 and CA125 in ovarian tumor patients

Abstract: Objective Survival in epithelial ovarian cancer (EOC) remains poor. Most patients are diagnosed in late stages. Early diagnosis increases the chance of survival. We used the proximity extension assay from Olink Proteomics to search for new protein biomarkers with the potential to improve the diagnostic performance of CA125 and HE4 in patients with ovarian tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…In the analysis of women who developed ovarian cancer less than 9 months after blood draw, nine biomarkers showed potentially useful discrimination, with AUC ≥ 0.70. Besides the well-established markers CA125 and HE4, four other markers in this list: (FR-alpha, KLK11, MDK and CXCL13) had been highlighted previously as having discrimination potential in several prior case-control comparisons using the Olink® Multiplex platforms [ 8 12 , 15 ], as well as in some further studies using other platforms [ 16 – 18 ]. We did not observe meaningful improvements in diagnostic performance by adding a single markers to CA125, particularly for ovarian cancer diagnosed more than 9 months after blood sampling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the analysis of women who developed ovarian cancer less than 9 months after blood draw, nine biomarkers showed potentially useful discrimination, with AUC ≥ 0.70. Besides the well-established markers CA125 and HE4, four other markers in this list: (FR-alpha, KLK11, MDK and CXCL13) had been highlighted previously as having discrimination potential in several prior case-control comparisons using the Olink® Multiplex platforms [ 8 12 , 15 ], as well as in some further studies using other platforms [ 16 – 18 ]. We did not observe meaningful improvements in diagnostic performance by adding a single markers to CA125, particularly for ovarian cancer diagnosed more than 9 months after blood sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Olink® Proteomics has developed a technology based on the proximity extension assay (PEA) [ 6 , 7 ], which permits the simultaneous measurement of up to 92 proteins in microliter volumes of blood serum or plasma. Several recent studies have used this multiplex platform to identify biomarkers for ovarian cancer detection, measuring candidate markers in blood samples collected from patients with clinically manifest ovarian cancer and from healthy controls or patients with benign pelvic conditions [ 8 12 ]. Using various (only partially overlapping) Olink® assay panels for sets of proteins relevant in oncology, inflammation and other disease areas, these studies identified several candidate proteins that, alone or in multi-marker panels, showed good discrimination between ovarian cancer patients and women with benign conditions or healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…High expression of ITGAV in ovarian cancer tumor tissue from late stage tumors has been associated with poor prognosis [37]. However, both tissue [38] and serum levels of ITGAV have been shown to be present at reduced levels in ovarian cancer compared to benign tumors and borderline ovarian cancers [39]. In addition, ITGAV expression has been correlated with increased expression of the matrix metalloprotease MMP9 in ovarian cancer effusions [40], which could impact ITGAV shedding into the serum in late stage ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of biomarkers, such as circulating miR-19a-3p and miR-483-5p, can enhance the diagnostic performance in various cancer types (59)(60)(61)(62). Notably, Chen et al (18) recently demonstrated that miR-650 combined with CA211 could be an effective diagnostic indicator for screening of the incidence of GC.…”
Section: Discussionmentioning
confidence: 99%